Routledge handbook of transnational organized crime - Allum, Felia, 1971-; Gilmour, Stan (London ; $a New York : Routledge, 2015)
"Transnational organized crime crosses borders, challenges States, exploits individuals, pursues profit, wrecks economies, destroys civil society, and ultimately weakens global democracy. It is a phenomenon that is all too often misunderstood and misrepresented. This handbook attempts to redress the balance, by providing a fresh and interdisciplinary overview of the problems which transnational organized crime represents. The innovative aspect of this handbook is not only its interdisciplinary nature but also the dialogue between international academics and practitioners that it presents. The handbook seeks to provide the definitive overview of transnational organized crime, including contributions from leading international scholars as well as emerging researchers. The work starts by examining the origins, concepts, contagion and evolution of transnational organized crime and then moves on to discuss the impact, governance and reactions of governments and their agencies, before looking to the future of transnational organized crime, and how the State will seek to respond."--Publisher's website.
Section I: Theories, Concepts, Definitions and Laws. Transnational Organized Crime as a Security Concept / Helena Carrapico ; Transnational Organized Crime: Thinking in and Out of Plato's Cave / Petrus C. van Duyne and Mark D.H. Nelemans ; Transnational Organized Crime and Social Sciences Myths / William J Chambliss and Elizabeth Williams ; A Survey of the Legal Standing of Transnational Organized Crime / Joseph Wheatley. -- Section II: Origins and Manifestations. The Many Faces of Organized Crime in Europe and its Assessment / Tom Vander Beken ; The Past and Present of Transnational Organized Crime in America / Mike Woodiwiss ; Transnational Organized Crime in Russia / Serguei Cheloukhine ; Nigerian Organized Crime / Stephen Ellis ; Transnational and Organized Crime in the Indo-Asia Pacific / Roderic Broadhurst, Sandy Gordon and John McFarlane ; Black Societies and Triad-like Organized Crime in China / Roderic Broadhurst. -- Section III: Contagion and Evolution. The Geography of Transnational Organized Crime: Spaces, Newtworks and Flows / Tim Hall ; The Practice of Transnational Organized Crime / Klaus von Lampe ; The Evolution of the International Drugs Trade: The Case of Colombia, 1930 -- 2000 / Michael Kenney ; The Human Trafficking- Organized Crime Nexus / Alexis A. Aronowitz ; Foundations and Evolution of the Crime-Terror Nexus / Tamara Makarenko ; A Bog of Conspiracy: The Institutional Evolution of Organized Crime in the UK / Dick Hobbs and Sue Hobbs ; Responding to Transnational Organized Crimes:'Follow the Money' / Margaret E Beare. -- Section IV: Intensity and Impact. Transnational Organized Crime and the Global Village / Kelly Hignett ; Transnational Organized Crime: Media, Myths and Moralities / Paddy Rawlinson ; Ethnicity, Migration and Transnational Organized Crime / Jana Arsovska ; Women and Transnational Organized Crime: The Ambigious Case of the Italian Mafias / Alessandra Dino ; Transnational Organized Crime and Alternative Culture Industry / Jason Pine. -- Section V: Governance. Civil Society and Transnational Organized Crime: The Case of the Italian Antimafia Movement / Jane Schneider and Peter Schneider ; Human Rights and the Policing of Transnational Organized Crime / Clive Harfield ; Criminalising People Smuggling: Preventing or Globalizing Harm? / Leanne Weber and Michael Grewcock ; The State and Transnational Organized Crime: the Case of Small Arms Trafficking / Dawn L. Rothe and Jeffrey Ian Ross ; Transnational Organized Crime and Terrorism / Angela Gendron ; Go with the Flow and Undo the Knots: Intelligence and Interconnectivity in Transnational Orgnaized Crime Policing / Monica den Boer ; Friends with Shared Aims? UK Experience Targeting Crime Overseas with Partner States -- the Need, the Roles and the Issue / Mark Bishop ; The Endangered Empire: American Responses to Transnational Organized Crime / Robert J. Kelly and Sharona A. Levy. -- Section VI: Reaction and Future. Local Policing and Transnational Organized Crime / Stan Gilmour and Robert France ; The Fight against Transnational Organized Crime in Italy: What Can we Learn? / Armando D'Alterio ; Mind the (information) Gap: Making Sense of the European Union's Strategic Approach to Transnational Organized Crime / Ben Goold ; The Fight against Transnational Organized Crime in Russa / Alexandra V. Orlova ; The Threat of Harm by Transnational Organized Criminals: A US Perspective / David A. Marvelli and James O. Finckenauer ; The Fight against Transnational Organized Crime in the Indo Asia Pacific: An Australian Perspective.
Includes bibliographical references and index.
Keywords: Transnational crime; Organized crime; Organized crime; Transnational crime